Do various groups involved in physics education appreciate the same aspects of physics demonstrations? A methodological approach - Nikitin, Alexandr; Snětinová, Marie (Scientia in educatione, 2025)
This paper presents a novel methodological approach to examining how different groups involved in upper secondary physics education perceive lecture demonstrations. The research utilizes a video-based, mixed-methods design that integrates high-inference rating scales and open-ended qualitative questions. This captures both holistic and analytical evaluations of demonstration quality. The paper focuses on the psychometric properties of the quantitative instrument and the alignment of ratings across four groups: secondary school students, in-service teachers, pre-service physics teachers, and teacher trainers. Initial findings suggest minimal statistically significant differences in how these groups evaluate physics demonstrations, indicating a potential universality in their perceptions. The methodological approach described in this paper offers a framework for assessing experiment focused lecture demonstrations. By providing insights into perceptions of teaching practices during demonstrations, this paper contributes to improving the design and delivery of physics demonstrations that engage diverse audiences and foster conceptual understanding.